Value-Based Transformation of Islamic Education Management in Strengthening the Governance of Contemporary Islamic Educational Institutions - Resi Dazia; Ali Mumin Budiman; Ade Aspandi; Dodi Suhendi (Journal of Educational Management Research, 2026)
This study aims to examine the transformation of Islamic Education Management based on values through the integration of the principle al-muhāfaẓah ‘alā al-qadīm aṣ-ṣāliḥ wa al-akhdzu bi al-jadīd al-aṣlaḥ in strengthening the governance of contemporary Islamic educational institutions. This research employs a qualitative approach with a library research design combined with a phenomenological perspective to understand the practical meaning of value implementation in institutional contexts. Data were collected from classical and contemporary literature, as well as reflections on management practices in Islamic educational institutions. Data analysis was conducted using content analysis and thematic analysis to identify patterns of integration between traditional values and modern innovation. The findings reveal that the principle has strong relevance as an operational foundation in managerial decision-making, enabling a balance between preserving Islamic values and adopting modern innovations. Value-based management transformation contributes to more transparent, accountable, and sustainable governance, while fostering a hybrid management model integrating normative, adaptive, and transformational dimensions. This study offers a conceptual contribution to the development of integrative Islamic Education Management and provides practical implications for maintaining institutional relevance and competitiveness in the digital era.